The Retranslation Hypothesis Revisited: Shakespeare’s Hamlet in Macedonian - Sonja Kitanovska-Kimovska (University “St. Kliment Ohridski“, Faculty of Education - Bitola, 2017)
Retranslation has most often been addressed in the field of literary translation in case studies of a single literary text, often described as a ‘classic’ (Koskinen & Paloposki 2010: 294). According to Paloposki & Koskinen (2004: 28), retranslation can be studied from at least two aspects: the reasons for retranslation and the profiles of retranslations. Questions that can be addressed include: what is the profile of retranslations compared to the profile of first translations in terms of domesticating or foreignising strategies and why are texts retranslated, as well as the context in which retranslations appear. In this paper I set out to address retranslation as a product in literary translation of classics by conducting a case study of the translations of Shakespeare’s Hamlet into Macedonian. I analyze the profiles of the translations to test the so called Retranslation Hypothesis. The analysis is based on a comparison between source text and target texts in terms of the number of lexical inventions, i.e. the number of words derived through the processes of conversion and compounding.
Keywords: retranslation, Hamlet, conversion, compounding